Serum vascular endothelial growth factor is a potential biomarker for acute mountain sickness - Nourkami-Tutdibi, Nasenien; Küllmer, Jennifer; Dietrich, Sven; Monz, Dominik; Zemlin, Michael; Tutdibi, Erol (Frontiers in Physiology, 2023)
Background: Acute mountain sickness (AMS) is the most common disease caused by hypobaric hypoxia (HH) in high-altitude (HA) associated with high mortality when progressing to high-altitude pulmonary edema (HAPE) and/or high-altitude cerebral edema (HACE). There is evidence for a role of pro- and anti-inflammatory cytokines in development of AMS, but biological pathways and molecular mechanisms underlying AMS remain elusive. We aimed to measure changes in blood cytokine levels and their possible association with the development of AMS. Method: 15 healthy mountaineers were included into this prospective clinical trial. All participants underwent baseline normoxic testing with venous EDTA blood sampling at the Bangor University in UK (69m). The participants started from Beni at an altitude of 869 m and trekked same routes in four groups the Dhaulagiri circuit in the Nepali Himalaya. Trekking a 14-day route, the mountaineers reached the final HA of 5050 m at the Hidden Valley Base Camp (HVBC). Venous EDTA blood sampling was performed after active ascent to HA the following morning after arrival at 5050 m (HVBC). A panel of 21 cytokines, chemokines and growth factors were assessed using Luminex system (IL-1β, IL-2, IL-4, IL-6, IL-8, IL-10, IL-12p40, IL-1ra, sIL-2Rα, IFN-γ, TNF-α, MCP-1, MIP-1α, MIP-1β, IP-10, G-CSF, GM-CSF, EGF, FGF-2, VEGF, and TGF-β1). Results: There was a significant main effect for the gradual ascent from sea-level (SL) to HA on nearly all cytokines. Serum levels for TNF-α, sIL-2Rα, G-CSF, VEGF, EGF, TGF-β1, IL-8, MCP-1, MIP-1β and IP-10 were significantly increased at HA compared to SL, whereas levels for IFN-γ and MIP-1α were significantly decreased. Serum VEGF was higher in AMS susceptible versus AMS resistant subjects (p<0.027, main effect of AMS) and increased after ascent to HA in both AMS groups (p<0.011, main effect of HA). Serum VEGF increased more from SL values in the AMS susceptible group than in the AMS resistant group (p<0.049, interaction effect). Conclusion: Cytokine concentrations are significantly altered in HA. Within short interval after ascent, cytokine concentrations in HH normalize to values at SL. VEGF is significantly increased in mountaineers suffering from AMS, indicating its potential role as a biomarker for AMS.